An evaluation of the global orientation of English textbooks in Germany. Issue 2 (3rd April 2018) - Syrbe, Mona; Rose, Heath
ABSTRACT: This article investigates textbooks used in English classes in German schools to evaluate their relevance to current trends of teaching English as an international language. For many European students, English is no longer just a foreign language, but an important European lingua franca. Thus, we argue it is essential for the language to be positioned as such in key textbooks used in English classrooms, which aim to prepare students for future use of English. An analysis of three main textbook series used in Germany was done through an adapted framework that depicts a Global Englishes approach to language teaching, focussing on representations of ownership, users, models, and target interlocutors of English. The analysis found that there was over-reliance of UK models of English, and static depictions of language users and cultures. The findings can be generalized to other countries where the sociolinguistic reality of English may not be accurately represented in English teaching materials.